Combate quimico de malezas en cebolla (Allium cepa L.) bajo riego en Alajuela - Rodriguez, A.M.=700 1 Soto, A.; Gamboa, C.J.
(Es, En)
Ilus., 13 ref.
Keywords: ALLIUM CEPA; MALEZAS; ESCARDA; CONTROL QUIMICO; RIEGO; COSTA RICA; AGRONOMIA COSTARRICENSE